2016
DOI: 10.1016/j.watres.2016.06.050
|View full text |Cite
|
Sign up to set email alerts
|

Effect of co-existing kaolinite and goethite on the aggregation of graphene oxide in the aquatic environment

Abstract: Broad applications of graphene oxide (GO) will result in the release of GO into aquatic environments, where clay minerals and metal (hydr)oxides are commonly present. Thereby the interactions between GO and a binary system containing clay minerals and metal (hydr)oxides can occur. We investigated the aggregation of GO with kaolinite and kaolinite-goethite associations (KGAs) in aquatic systems under different pHs, ionic strengths, and GO concentrations. GO suspension was unstable at low pHs, and the aggregatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(46 citation statements)
references
References 37 publications
1
45
0
Order By: Relevance
“…Graphene has a high theoretical specific surface area and excellent electrical conductivity and is an ideal CDI electrode material. However, due to the aggregation effect of graphene, the actual specific surface area is much lower than the theoretical value . The preparation of graphene into a 3D network structure or composite can overcome the abovementioned aggregation effect and improve the desalination performance.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Graphene has a high theoretical specific surface area and excellent electrical conductivity and is an ideal CDI electrode material. However, due to the aggregation effect of graphene, the actual specific surface area is much lower than the theoretical value . The preparation of graphene into a 3D network structure or composite can overcome the abovementioned aggregation effect and improve the desalination performance.…”
Section: Introductionmentioning
confidence: 98%
“…However, due to the aggregation effect of graphene, the actual specific surface area is much lower than the theoretical value. [25][26][27] The preparation of graphene into a 3D network structure or composite can overcome the abovementioned aggregation effect [28][29][30][31] and improve the desalination performance. However, the conventional 3D graphene has a relatively large pore structure, which makes the electrode material unable to interact well with anions and cations during the desalination process, thereby affecting the CDI performance of the 3D graphene.…”
Section: Introductionmentioning
confidence: 99%
“…Agglomeration and stability of fullerene (nC 60 ) (Anderson and Barron, 2005; Bouchard et al, 2009; Chen and Elimelech, 2006, 2008, 2009), carbon nanotube (CNT) (Sano et al, 2001; Smith et al, 2008; Smith et al, 2009), and graphene oxide (GO) (Chowdhury et al, 2013; Chowdhury et al, 2015; Huang et al, 2016; Konkena and Vasudevan, 2012; Wu et al, 2013) have been extensively studied in the literature. These studies showed that the agglomeration of CNMs follows the Derjaguin-Landau-Verwey-Overbeek (DLVO) theory, and the CNM-specific properties have strong effects on the colloidal stability of CNMs.…”
Section: Introductionmentioning
confidence: 99%
“…In all the cases, LDH-Cl was better than LDH-CO 3 , perhaps because the first one was more positively charged than the later. Huang et al [30] performed similar experiments with kaolinite and goethite associated with kaolinite (10% or 4% goethite) in a mixture of deionised water bearing 20 mg/L of GO, 2000 mg/L of mineral and with pH adjustment. It was found that, after 24 h, GO sheets could be aggregated in presence of kaolinite, kaolinite with 4% goethite and kaolinite with 10% goethite if pH was lower than 4, 5 and 6, respectively.…”
Section: Figurementioning
confidence: 99%